2020
DOI: 10.3389/fonc.2020.554759
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of lncRNA–Mediated ceRNA Network in Lung Adenocarcinoma

Abstract: Background: A growing body of evidence indicates that long non-coding RNAs (lncRNAs) can act as competitive endogenous RNAs (ceRNAs) to bind to microRNAs (miRNAs), thereby affecting and regulating the expression of target genes. The lncRNA-miRNA-mRNA ceRNA network has been theorized to play an indispensable role in many types of tumors. However, the role of the lncRNA-related ceRNA regulatory network in lung adenocarcinoma (LUAD) remains unclear. Methods: We downloaded the RNAseq and miRNAseq data of LUAD from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 47 publications
2
97
0
Order By: Relevance
“…The decreased probability of the OS of patients with LUAD in GEO is consistent with the findings observed in TCGA-LUAD data. However, we observed no overlapping mRNAs or lncRNAs with a previous study that did similar research on LUAD by constructing a ceRNA network with DEGs using Cytoscape [ 38 ]. This might be caused by the following reasons: the definitions set by the two studies were different (we set ∣log 2 FC | >1.5 instead of ∣log 2 FC | >2); we added two processes before ceRNA network construction, including collecting LUAD-related genes (with differential expression) based on WGCNA and evaluating the prognostic value of genes with univariate Cox regression; when constructing the ceRNA network, besides interactions predicted by the database, two rules (the correlation between the expression of lncRNAs and mRNAs and similar roles of miRNAs in regulating their corresponding lncRNAs and mRNAs) were considered.…”
Section: Discussionsupporting
confidence: 44%
“…The decreased probability of the OS of patients with LUAD in GEO is consistent with the findings observed in TCGA-LUAD data. However, we observed no overlapping mRNAs or lncRNAs with a previous study that did similar research on LUAD by constructing a ceRNA network with DEGs using Cytoscape [ 38 ]. This might be caused by the following reasons: the definitions set by the two studies were different (we set ∣log 2 FC | >1.5 instead of ∣log 2 FC | >2); we added two processes before ceRNA network construction, including collecting LUAD-related genes (with differential expression) based on WGCNA and evaluating the prognostic value of genes with univariate Cox regression; when constructing the ceRNA network, besides interactions predicted by the database, two rules (the correlation between the expression of lncRNAs and mRNAs and similar roles of miRNAs in regulating their corresponding lncRNAs and mRNAs) were considered.…”
Section: Discussionsupporting
confidence: 44%
“…At present, a large number of studies have found that the occurrence and metastasis of lung cancer are affected not only by genes, but also by external factors such as small RNA and long non-coding RNA. A lot of evidence shows that they play an important role in a variety of diseases (28). In recent years, the function of lncRNA in life activities has been continuously discovered with the extensive development of research.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with several previous studies, our approach has the following improvements. First, for constructing the ceRNA network, we used only negatively correlated lncRNAs/mRNAs-miRNAs regulatory pairs, which fits well the definition of the ceRNA network compared to the previous method without this distinction Fan et al, 2020;Wu et al, 2020). Second, we applied 1,000 rounds of lasso-Cox regression model fittings to identify the optimal lncRNA-based set, which is deemed to be more robust than the conventional Cox model utilized in a previous study (Zheng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%